The Effectiveness of the Learning Strategy "Think, Talk, Write" and Snowball for Improving Learning Achievement in Lessons Insya' at Islamic Boarding School Arisalah - Fitrianto, Ibnu; 'Aimah, Syamsul; Hamid, Riza; Mulalic, Ahmad (International Journal of Post Axial: Futuristic Teaching and Learning, 2023)
This study aims to determine the effectiveness of the learning strategy "think, talk, write" and snow ball for improving learning achievement. This study uses an experimental method with a quantitative approach. The population of this study was the fifth grade students of Pondok Modern Arrisalah Ponorogo, while the sampling technique was startified by random sampling. The data analysis used the Kruskal Wallis and Mann Whitney test. The results of this study are: (1) The use of learning strategies "think talk write" and snowball throwing which is based on a communicative approach and conventional learning is effective in increasing student scores, this is based on the results of the Kruskal Wallis Test. (2) The results of the Mann-Whitney Test show that there is no difference between student learning outcomes using the "think talk write" and snowball throwing learning strategies which are based on a communicative approach. (3) There is a difference between learning outcomes using the learning strategy "think talk write" which is based on a communicative approach and conventional learning (4) There is a difference between student learning outcomes using the snowball throwing learning strategy which is based on a communicative approach and conventional learning. Suggest to teachers should have creativity and educational innovation, because the educational strategy will develop with the development of time.